Towards local sustainability: Social capital as a community insurance in Kazakhstan. Issue 2 (July 2021) - Darmenova, Yuliya; Koo, EunJoo
This article focuses on how social capital, in the form of trust, reciprocal relations, and networks, has contributed to the sustainability of local communities in Kazakhstan in the face of various political and socioeconomic challenges. Drawing on qualitative data, we provide historical evidence of the persistence of locally derived social capital and investigate the ways in which it contributed to local sustainability in Kazakhstan. We first discuss how people in Kazakhstan have historically built and developed networks, reciprocal relations, and mutual trust under different political and economic institutions, for example, in the form of reciprocal labor aid as part of nomadic culture (e.g., "Asar") and collective funds (e.g., "Kotel") during Soviet times. We then offer an in-depth understanding of social capital as a form of insurance for local communities, and how it facilitates socioeconomic interactions in contemporary Kazakh society. This study contributes to the understanding of this traditional sense of trust and communal cooperation, as well as its viability in the context of a market economy.